1997
DOI: 10.1007/s004280050108
|View full text |Cite
|
Sign up to set email alerts
|

TUNEL-positive hepatocytes in alcoholic liver disease

Abstract: Alcohol-induced damage to the liver results in a wide array of typical alterations. Whereas the mechanisms involved in the pathogenesis of fatty change, hepatocyte ballooning, Mallory body formation and fibrosis have been studied in detail, little is known about hepatocyte apoptosis in alcoholic liver disease (ALD). In this retrospective study we analysed parenchymal cell death in ALD systematically by the use of in situ DNA nickend labelling (ISEL/TUNEL). We show that increased hepatocyte TdT labelling occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…DNA damage may be incurred due to exposure of the hepatocytes to ethanol intoxication-induced oxidative stress, causing the production of ROS and TNF-α-induced cell death, resulting in hepatic damage [26]. The current study showed that the ethanol intoxication of mouse hepatocytes increased the number of apoptotic cells observed with the TUNEL assay and phase-contrast microscopy, which is consistent with the literature using human alcoholic hepatitis specimens [42,43]. However, in the current study, when pre-treated with either Silymarin or BERM, a substantial decrease in the number of ethanol-induced apoptotic cells was noticed, confirming the in vivo hepatoprotective effect of BERM against alcohol intoxication.…”
Section: Discussionsupporting
confidence: 91%
“…DNA damage may be incurred due to exposure of the hepatocytes to ethanol intoxication-induced oxidative stress, causing the production of ROS and TNF-α-induced cell death, resulting in hepatic damage [26]. The current study showed that the ethanol intoxication of mouse hepatocytes increased the number of apoptotic cells observed with the TUNEL assay and phase-contrast microscopy, which is consistent with the literature using human alcoholic hepatitis specimens [42,43]. However, in the current study, when pre-treated with either Silymarin or BERM, a substantial decrease in the number of ethanol-induced apoptotic cells was noticed, confirming the in vivo hepatoprotective effect of BERM against alcohol intoxication.…”
Section: Discussionsupporting
confidence: 91%
“…Although, SPARC like 1 is barely expressed in normal liver, significance of its overexpression in HCC is not well studied. Overexpression of tenascin C and type IV collagen induces a defective extracellular matrix pattern in hepatocellular cancer . Other major overexpressed proteins in HCC were vitronectin and fibronectin, which are involved in cell migration and adhesion in HCC along with other basement membrane proteins such as collagen IV and laminin. …”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that chronic ethanol consumption increases apoptosis of hepatocytes in mice (Goldin et al, 1993;Deaciuc et al, 2001); rats (Benedetti et al, 1988;Kurose et al, 1997;Mi et al, 2000;Slomiany et al, 1999;Yacoub et al, 1995); minipigs (Halsted et al, 1996), and humans (Zhao et al, 1997), the numbers of apoptotic hepatocytes are small. Others (Rashid et al, 1999) have shown, and we have con®rmed here (Figure 2), that there is no signi®cant apoptosis in the liver of mice fed chronically with the DeCarli-Lieber ethanol containing liquid diet.…”
Section: Discussionmentioning
confidence: 99%